Pengaruh Pembelajaran Pendidikan Kewarganegaraan Terhadap Peningkatan Karakter Mahasiswa PPKN Unimed - Ruth Yessika Siahaan; Chairun Nisa; Muthia Lathifah; Jojor Mindo Manullang (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
Citizenship Education (PKn) has an important role in forming national character. This research aims to identify the influence of Citizenship Education learning on improving the character of Citizenship Education Program (PPKN) students at Medan State University (UNIMED). The research method used is quantitative analysis using a questionnaire to collect data from UNIMED PPKN students. The results of the research show that learning Citizenship Education has a significant positive influence on improving student character. These findings provide an important contribution in strengthening the role of Citizenship Education in shaping student character, as well as providing a basis for developing more effective learning strategies in the future. It is hoped that this research can provide useful insights for curriculum development and learning of Citizenship Education in higher education environments.